Standards of the Validity of Criminal Procedural Decisions in Criminal Proceedings - Hetman, Halyna (Problems of legality, 2025)
The article is devoted to determining the standards of reasonableness of decisions in criminal proceedings. Research into the issues of making lawful and reasonable decisions as acts of application of law in criminal procedure at the national level dates back to the 60s of the last century. However, the issues of legality and validity of such decisions by the subjects authorised by the State continue to be the subject of debate among scholars and practitioners, despite a significant number of studies in this area and scientific research in defining the content of such a concept as ‘justification’. It is appropriate to state that despite the large number of studies conducted and the high quality of the developed recommendations, in practice there are problems with making criminal procedural decisions and their justification in the form of procedural documents, misinterpretation of national legislation, low awareness of the decisions of the European Court of Human Rights (hereinafter - ECHR), which are manifested in the refusal of investigating judges to satisfy motions for the application of measures to ensure criminal proceedings, detention of persons, and other issues. This, in turn, leads to an appeal against such activities of the State representatives to the ECHR if such actions of the State violate the rights guaranteed by Articles 3 and 5 of the Convention for the Protection of Human Rights and Fundamental Freedoms. The article also analyses the ECHR judgments which set out the standard of reasonableness of decisions during detention of a person, which must be observed by the relevant subjects of criminal proceedings authorised to perform such procedural actions. However, the number of applications received annually by the European Court of Human Rights regarding violations of Articles 3 and 5 of the Convention gives grounds to assert that the participating States, represented by the relevant authorised bodies, do not comply with the developed standards of reasonableness of decisions and are proportionally illegal, which in turn leads to violations of human rights and freedoms. Although, as is well known, the judgments of the European Court of Human Rights are binding. In order to carry out a proper review of the ECHR case-law on the reasonableness of decisions in criminal proceedings, we have analysed the content of a criminal procedural decision in general under the current criminal procedural legislation of Ukraine, identified its types, features and highlighted the ECHR standards which must be taken into account when reasoning a criminal procedural decision.